IDENTIFIKASI KEANEKARAGAMAN DAN POLA SEBARAN BURUNG YANG TERDAPAT DI KAWASAN JALUR PENDAKIAN KAWAH RATU TAMAN NASIONAL GUNUNG HALIMUN SALAK, CIDAHU, SUKABUMI - Novira, Rahmi; Uki Sajiman, Supardi; Indar Praditya, Dimas; Dwi Kurnia, Tika (Lafadz Jaya Publisher, 2023)
Birds are one of the biological assets owned in Indonesia. The existence of feed, nesting places and layouts are factors that influence bird species richness at the local level. This study aims to determine the types, populations and distribution of birds found in the Crater of Queen TNGHS Climbing Trail, Cidahu, Sukabumi. This observation uses a fixed distance